Kimura Disease: A Rare Case with Multiple Recurrences involving Subcutaneous Tissue, Parotid Gland, and Lymph Nodes - Sukanya Das; Mahesh Chavan; Vikram V. Khare; Trupti Gaikwad (Wolters Kluwer Medknow Publications, 2024)
Kimura disease (KD) is an uncommon, long-standing inflammatory condition affecting the head and neck that has no recognized cause. It typically appears as a painless subcutaneous nodule mimicking a tumor. The characteristic triad other the painless subcutaneous masses include elevated serum immunoglobulin E and peripheral eosinophilia. We present a unique instance of KD involving a male individual, age 23 years, who has swelling in the pre-auricular area on the left side of the face. Establishing KD as a probable differential diagnosis is the key to prompt treatment, declining misdiagnosis, and enhancing the quality of the patient's life.